A Novel Approach to Monitor and Maintain Database About Physiological Parameters of (Javelin) Athletes Using Internet of Things (IoT) - Elumalai, G.; Ramakrishnan, R. (Wireless personal communications, 2020)
Real time monitoring of physiological parameters is very important to safeguard Athlete’s life time from severe life-threatening diseases and injuries during training and competitions. Now a day, sensors play a pivotal role in sports for online monitoring of physiological and movement parameters. To improve the performance of athletes, continuous monitoring of physiological parameters and providing feedback are more important. This study mainly concentrates on javelin throw, which is one of the track and field events. Due to poor training and lack of best coaches, javelin athletes do not shine in the Olympics. Javelin athletes have to balance both physiological and movement parameters to achieve maximum distance while throwing the javelin. We design a hardware using sensors and Arduino controller to monitor physiological parameters such as blood pressure, heart rate and electrocardiogram. Using SQL database and internet of things the measured parameters are stored in web server for further analysis and providing feedback to athletes. The aim of this study is to bridge the gap between Engineering and sports technology and provide a collaborative platform for the sharing of knowledge, so that both Coaches and athletes can get the benefited.